(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This essay focuses on the Transidentity context, addressing characteristics about the construction of Trans women in society. It enters the Trans identity, or gender-divergent, which is historically stigmatized. Different perspectives about culture and identity are analyzed, and how these categories are presented in the experiences of the identities mentioned above. The methodology mixes analysis and interpretation. Through analysis, concepts are clarified, especially that of identity and culture, paying attention to their interconnections. Through hermeneutics, these concepts are interpreted for an understanding in which cracks open to the optics of alterity and a look that transcends the binary perspective, as well as the contributions of the Transfeminist movement in the realization of Transidentitarian rights.